Inventory of Rattan in the Depati Karo Jayo Tuo Customary Forest, Rantau Kermas Village - Nur Apriani; Mahya Ihsan; Uni Baroroh Husnudin; Bambang Hariyadi; Pinta Murni (Universitas Labuhanbatu, 2025)
The Depati Karo Jayo Tuo Customary Forest, located within the Merangin Geopark, is a conservation forest that contains various plant species, including rattan. However, specific data on rattan species in this area are unavailable. This study aims to inventory and categorize the rattan species in the forest. Data collection was carried out by exploring the forest's trekking path. Rattan samples were collected using the quadrat plot method. The identification results revealed the presence of seven rattan species in the Depati Karo Jayo Tuo Customary Forest, namely Calamus micracanthus Griff., Calamus javensis Blume, Calamus oblongus Reinw. ex Blume, Calamus manan Miq., Calamus castaneus Griff., Calamus sp., and Korthalsia laciniosa (Griff.) Mart. Among these, Calamus oblongus Reinw. ex Blume was the most abundant species, with 1,050 individuals, while Calamus castaneus Griff. was the least abundant, with only 14 individuals recorded. According to the IUCN conservation status, all identified rattan species are classified as